Validation Of Established Methods For Determination Of Fine Particle Breakage - Rashid, Noor Adilah (Universiti Sains Malaysia, 2017)
The objective of the study is to validate two methods which have already been establish to study the breakage behaviour of materials and study the effect of particle size on the breakage of particles. In this case, it focuses on fine particle breakage. As any size reduction process consumes much energy, JKMRC initiated the study of breakage behaviour of material. Laboratory ore characterization tests are derived for this purposes; bed breakage and single particle breakage. Result of these tests would produce the date that is needed for the particle size analysis. From this analysis, t10 values- fineness index will be created and used to compute the a, b parameters. These parameters are then finally being used to get the breakage function. Result of breakage function displays the same breakage function value for bed breakage method. Hence, size doesn‘t affect the breakage in bed breakage. However, result of single particle breakage shows a slight difference of breakage function value for the different size. The difference is so small that it is considered as not significant. This leads to a conclusion that, both methods are suitable to determine the breakage behavior and size does not affect the breakage of particles for both methods.